SCG Mosquito Trap: A New Lethal Ovitrap for Controlling Aedes aegypti (L.) and Ae. albopictus (Skuse); the Vectors of Dengue Haemorrhagic Fever, and Chikungunya and Zika Fever - Tawatsin, Apiwat; Thavara, Usavadee; Srivarom, Navy (British Journal of Healthcare and Medical Research, 2022)
Aedes aegypti (L.) and Ae. albopictus (Skuse) are known to be the vectors of dengue haemorrhagic fever (DHF), and chikungunya and zika fever. Of these diseases, DHF is the most dangerous because it has high incidence and mortality in many countries worldwide, especially in Asia. As there is currently no effective vaccine available to prevent these diseases, vector control is the best strategy for controlling them. Therefore, the SCG Mosquito Trap: a new lethal ovitrap combined with attractant and biological larvicide, was developed in this study for controlling Ae. aegypti and Ae. albopictus mosquitoes. The trap without attractant showed significantly higher oviposition efficacy than that of a conventional one in luring gravid Ae. aegypti and Ae. Albopictus to lay their eggs under laboratory conditions by approximately 3.1 and 2.6 times, respectively. The attractant derived from carpet shell extract increased the oviposition efficacy of the SCG Mosquito Trap by about 1.7 and 4.1 times against Ae. aegypti and Ae. albopictus, respectively, under laboratory conditions. Bacillus thuringiensis israelensis (Bti) was the biological larvicide used in the SCG Mosquito Trap. It provided a complete killing effect (100% mortality) against the larvae of Ae. aegypti and Ae. albopictus for 4 weeks post single application, as no larvae hatched from sponge sheets applied with Bti, which were obtained from the SCG Mosquito Trap. In the field study against Ae. aegypti, the SCG Mosquito Trap could reduce the number of houses infested from 80% (with 75% from the positive trap and an average of 242 eggs/trap) to 30% (with 22.5% from the positive trap and an average of 64 eggs/trap) by the fourth week after initiation. In conclusion, the SCG Mosquito Trap developed from this study could be used additionally as an effective device for controlling Ae. aegypti and Ae. albopictus mosquitoes, in order to prevent the diseases that are transmitted by these vectors.